2020
DOI: 10.1155/2020/9185707
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Mechanisms of Chinese Herbal Medicine Dingji Fumai Decoction

Abstract: Background. Dingji Fumai decoction (DFD) is used to treat ventricular arrhythmia, and it has provided a very good curative effect. However, its cellular electrophysiological mechanism is unknown. Methods. Electrocardiogram was recorded, and oxidative stress response and ion-channel-related molecules were detected in rats with barium chloride- and aconitine-induced ventricular arrhythmia. Moreover, whole-cell patch-clamp assay was used to investigate the inhibitory effect of DFD on Nav1.5 in Chinese hamster ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…Dingji Fumai Decoction (DFD), consisting of Chuanxiong Rhizoma (Chuanxiong), Jujubae Fructus (Dazao), Poria Cocos (Schw. ), Wolf (Fuling), Cinnamomi Ramulus (Guizhi), Silktree Albizia Bark (Hehuanpi), Osdraconis (Fossiliaossiamastodi) (Longgu), Ostrea Gigas Thunberg (Muli), Ziziphi Spinosae Semen (Suanzaoren), Radix Polygalae (Yuanzhi), and Licorice (Gancao), is widely used for VA. Our previous work con red its e cacy and safety on VA 25 , and one of the underling mechanisms is class I antiarrhythmic property 26 . To make DFD more recognized, it is essential to make the e cacy and safety of DFD clearly.…”
Section: Introductionmentioning
confidence: 96%
“…Dingji Fumai Decoction (DFD), consisting of Chuanxiong Rhizoma (Chuanxiong), Jujubae Fructus (Dazao), Poria Cocos (Schw. ), Wolf (Fuling), Cinnamomi Ramulus (Guizhi), Silktree Albizia Bark (Hehuanpi), Osdraconis (Fossiliaossiamastodi) (Longgu), Ostrea Gigas Thunberg (Muli), Ziziphi Spinosae Semen (Suanzaoren), Radix Polygalae (Yuanzhi), and Licorice (Gancao), is widely used for VA. Our previous work con red its e cacy and safety on VA 25 , and one of the underling mechanisms is class I antiarrhythmic property 26 . To make DFD more recognized, it is essential to make the e cacy and safety of DFD clearly.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, DFD, as a traditional Chinese decoction, treats VA through multicomponent and multitarget, indicating that the underlying mechanisms are complex as described in our present study. Although we have made some identification on the mechanisms [25], 6…”
Section: Discussionmentioning
confidence: 96%
“…Dingji Fumai Decoction (DFD), consisting of Chuanxiong Rhizoma (Chuanxiong), Jujubae Fructus (Dazao), Poria cocos (Schw.) Wolf (Fuling), Cinnamomi Ramulus (Guizhi), Silktree Albizia Bark (Hehuanpi), Osdraconis ( Fossiliaossiamastodi ) (Longgu), Ostrea Gigas Thunberg (Muli), Ziziphi Spinosae Semen (Suanzaoren), Radix Polygalae (Yuanzhi), and Licorice (Gancao), is widely used for VA and obtains encouraging results [ 24 ], and previous experiments revealed that one of the underlying mechanisms is class I antiarrhythmic property [ 25 ]. To make DFD more recognized, it is essential to ensure the efficacy and safety of DFD.…”
Section: Introductionmentioning
confidence: 99%
“…High-performance liquid chromatography (HPLC) fingerprints of GXV HPLC fingerprints of GXV were performed as described previously [25,56,57] with some modifications.…”
Section: Functional Enrichmentmentioning
confidence: 99%
“…Network pharmacology is of great significance for the discovery of effective components and potential targets in TCM and the investigation of its underlying mechanisms, which may help explore the pharmacological properties of herbal medicines [23,24]. In view of the complex composition of TCM, it has the characteristics of multitarget, multichannel and coordination and synergism [25][26][27][28]. With the continuous improvement in the natural science system, the study of in-depth drug disease mechanisms is increasing [29].…”
Section: Introductionmentioning
confidence: 99%